Microstructural and topographic characterization of concrete protected by acrylic paint - Carmen Couto Ribeiro (Materials Research, 2013)
Concrete structures must be designed and constructed so as to resist the conditions established in the project design and suffer no deterioration for many years. In highly aggressive environments, in addition to the minimum layer covering the framework, the concrete must receive a protective coating. In this work, the efficiency of acrylic paint as a protective coating, while the concrete was placed in an aggressive environment, was assessed utilizing a profilometric and microstructural characterization. The concrete was dosed using the ACI - American Concrete Institute method. The specimens were prepared with 370 kg.m-3 of cement and the water-binder ratio of 0.50 corresponds to the value established in NBR6118¹ types for concrete subjected to highly aggressive environments. With the use of profilometry, 3D topographical images and surface roughness parameters were generated, which allowed for the identification of the degradation process and the minimization of the effect of this attack on concrete that had received surface protection. The topographic roughness parameters, as well as the images and chemical components identified using SEM/EDS, made it possible to identify the process of deterioration of the concrete under acid attack and to minimize such effect in the coated concrete. The methodology adopted demonstrates that the application of acrylic paint as a protective coating for concrete in an aggressive environment minimizes its surface degradation and increases its durability.